Teacher self-renewal capacity: Principal’s learning supervision strategies in elementary schools - Sahirah, Nahdah Nasya; Suryana, Asep; Sutarsih, Cicih (Journal of Educational Management and Instruction (JEMIN), 2025)
The low competency of teachers in Indonesia indicates the need to improve teacher quality through self-renewal led by principals; however, the current fulfillment of teacher needs still prioritizes quantity over quality, and many teachers face obstacles in achieving self-renewal. This study describes the principal's learning supervision strategy in fostering teacher self-renewal capacity. This research method uses qualitative data collection techniques through observation, interviews, and documentation, involving 7 informants: the principal, 4 teachers, and 1 staff member at Public Elementary School (SDN) 035 Soka, Bandung City Indonesia, selected through purposive sampling. Data analysis in this study used the Miles & Huberman model and the data processing employed Nvivo 14 application. The results of this study indicate that the principal implements collaborative strategies in every stage of learning supervision to foster teacher self-renewal capacity. Teachers at SDN 035 Soka have teacher self-renewal capacity, which can be seen from their ability to continue learning and adapting to educational developments by improving their performance through exploitation, exploration, absorption, integration, and leadership. This research provides important implications for the development of learning supervision strategies and the enhancement of teachers' self-renewal capacity. These findings can serve as a reference for school principals to support teachers' professional development and improve the quality of teaching in schools.